2022
DOI: 10.7759/cureus.22636
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis-Induced Colorectal Carcinoma: A Deleterious Concatenation

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory gastrointestinal ailment that encompasses Crohn's disease (CD) and ulcerative colitis (UC). UC is an idiopathic, chronic inflammatory condition of the colonic mucosa that begins in the rectum and progresses proximally in a continuous way over a portion of the entire colon. Chronic inflammation is linked to cancer, and IBD-related chronic colonic inflammation raises the risk of colorectal cancer. Chronic inflammation has been linked to cancer, and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In conclusion, chronic inflammation, the main pathological process of UC, may lead to the accumulation of high levels of proinflammatory cytokines within the colonic mucosa and could lead to cancer. The risk of colorectal cancer (CRC) in patients with UC is 2.4-fold higher compared to the general population [ 2 ]. Improving inflammatory response is a viable approach for the treatment of UC and prevention of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In conclusion, chronic inflammation, the main pathological process of UC, may lead to the accumulation of high levels of proinflammatory cytokines within the colonic mucosa and could lead to cancer. The risk of colorectal cancer (CRC) in patients with UC is 2.4-fold higher compared to the general population [ 2 ]. Improving inflammatory response is a viable approach for the treatment of UC and prevention of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First-line therapy includes 5-aminosalicylic acid and corticosteroids. Glucocorticoids and biological agents can be added when 5-aminosalicylic acid therapy is ineffective [ 2 ]. Because of the marked side effects of Western medicine, patients still have difficulty adhering to treatment, leading to the discontinuation of therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data obtained from experimental methods such as SHAPE can be used to constrain RNA-RNA interaction prediction. SHAPE directed homology and motif analysis has recently become the preferred method for identifying local RNA-RNA interactions and structures [ 20 ]. Often, SHAPE constrained predictions focus on local RNA structure and accessibility; however, it has been shown that long-range RNA-RNA interactions can also be obtained using SHAPE methods [ 17 ].…”
Section: Introductionmentioning
confidence: 99%